1979
DOI: 10.1007/bf02618149
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microvessels and derived cells in tissue culture: Isolation and preliminary characterization

Abstract: Microvessels isolated from mouse forebrain were used as the source material for the derivation of cerebral vascular endothelium and smooth-muscle cells in culture. The microvessels were isolated by a mechanical dispersion and filtration technique, and were maintained in vitro as organoid cultures. A microvessel classification system was developed and proved to be useful as a tool in monitoring culture progress and in predicting the type(s) of microvessel(s) that would give rise to migrating and/or proliferatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
1
1

Year Published

1983
1983
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(45 citation statements)
references
References 19 publications
1
42
1
1
Order By: Relevance
“…Removal of the medium and unattached cells 30 min after inoculation helped to select for endothelial cells. Although previous studies with capillary endothelium have reported the requirement for gelatin, collagen, or other substratum materials (19,27), in our hands the RCME cells attached as well to untreated culture plates. The primary cultures required high serum concentrations (15-20%) to support growth.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…Removal of the medium and unattached cells 30 min after inoculation helped to select for endothelial cells. Although previous studies with capillary endothelium have reported the requirement for gelatin, collagen, or other substratum materials (19,27), in our hands the RCME cells attached as well to untreated culture plates. The primary cultures required high serum concentrations (15-20%) to support growth.…”
Section: Resultscontrasting
confidence: 68%
“…In the past 3 to 4 yr, rapid progress has been made in the isolation and culture of microvascular endothelial cells (17)(18)(19)(20)(21)(22)(23)(24)(25). These studies have demonstrated that microvascular endothelial cells exhibit several fundamental differences potentially useful for the understanding and treatment of diseases with a microvascular component.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure used for the isolation of the microves sels was derived from the method of Debault et al (1979). The cortex, cleared of the meninges, was cut into small pieces and washed with a phosphate-buffered salt solution (PBS) of pH 7.0 containing 2 giL glucose and 0.…”
Section: Culture Of Cells Derived From Cortical Microvesselsmentioning
confidence: 99%
“…[6][7][8] Cell Cultures. The mouse brain endothelial cell line MBE-1 (called MBE), isolated in our laboratory by J. Joseph (4,5,13), was obtained from cerebral microvessels of strain A.TL mice according to published protocols of DeBault et al (14). After initial culture in modified Lewis medium (14), the line was maintained in Dulbecco's modification of Eagle's minimum essential medium (DME medium) supplemented with 15-20% fetal bovine serum and 20% S-180 tumor-conditioned medium as described by Folkman et al (15).…”
mentioning
confidence: 99%
“…FB-356 fibroblasts exposed to 5000 rad of y-irradiation served as feeder layers for teratoma cell lines. M-5076 cells were grown in DeBault's medium (14) but could be maintained in primary culture only.…”
mentioning
confidence: 99%